Synthesis, structural characterization, and cytotoxic activity in tumor cells of Cu(II) and Co(II) complexes with o‐vanillin amino acids Schiff bases. (19th August 2022) - Dinev, Desislav; Popova, Katya B.; Zhivkova, Tanya; Dyakova, Lora; Abudalleh, Abedullkader; Alexandrova, Radostina; Culita, Daniela C.; Mocanu, Teodora; Maxim, Catalin; Marinescu, Gabriela
Abstract : Two new families of Cu(II) and Co(II) mononuclear complexes with mixed ligands, [Cu(VanTrpt)(bipy)]·MeOH (CuVanTrpt ), [Cu(VanSer)(bipy)]·4H2 O (CuVanSer ), [Cu(VanTyr)(bipy)]·H2 O (CuVanTyr ), [Cu(VanThr)(bipy)]·MeOH (CuVanThr ), [Co(VanTrpt)(bipy)(OH2 )]·H2 O·MeOH (CoVanTrpt ), [Co(VanSer)(bipy)(OH2 )]·MeOH (CoVanSer ), [Co(VanTyr)(bipy)(OH2 )]·3H2 O·MeOH (CoVanTyr ), and [Co(VanThr)(bipy)(OH2 )] (CoVanThr ), (VanX are Schiff base proligands resulted from the condensation of o ‐vanillin with D, L‐tryptophan (VanTrpt), L‐serine (VanSer), L‐tyrosine (VanTyr), and L‐threonine (VanThr), respectively, and bipy is 2, 2′‐bipyridine), have been obtained and characterized on the basis of elemental analysis, magnetic measurements, and spectral data (FT‐IR and UV–Vis–Nir spectroscopy). Crystal structures of CuVanTrpt, CuVanSer, and CuVanTyr have been solved by single‐crystal X‐Ray diffraction. Biological evaluation revealed that they are cytotoxic in HeLa (human carcinoma of the uterine cervix) and LSR‐SF‐SR (rat sarcoma induced by Rous sarcoma virus strain Schmidt‐Ruppin) cells, showing an enhancement of cytotoxicity dependent of concentration and treatment time. The most pronounced cytotoxic effect is expressed by CuVanSer and CoVanSe r. Various cytopathological changes of both types of cancer cells were observed after treatment with Cu(II) and Co(II) complexes for 72 h at concentrations of 100 and 200 μg ml −1 . LSR‐SF‐SR cells were found to be relatively more sensitive to the cytotoxic effect of the complexes investigated as compared to HeLa cells. Abstract : Two new families of Cu(II) and Co(II) mononuclear heteroleptic complexes, with amino acids o ‐vanillin Schiff bases and 2, 2′‐bipyridine have been synthesized and structurally characterized. Biological evaluation revealed their cytotoxicity against HeLa and LSR‐SF‐SR cell lines. The most pronounced cytotoxic effect is expressed by CuVanSer and CoVanSer . LSR‐SF‐SR cells were found to be relatively more sensitive to the cytotoxic effect of the complexes investigated as compared to HeLa cells.